Patterns of Drug Misuse and the School Drop-out - Loken, Joel (Canadian Journal of Counselling and Psychotherapy, 2012)
In addition to studying the prevalence of drug abuse among transient youth this study attempted to relate certain drug-use patterns to the student drop-out rates. We tried to determine why students leave school and when. We investigated new drug use patterns.